The Service User as a Partner in Social Work Projects and Education Concepts and Evaluations of Courses with a Gap-Mending Approach in Europe - Chiapparini, Emanuela (Verlag Barbara Budrich, 2016)
To become a competent social worker it is essential to know the perspective of the service users. Therefore, service users are more and more included in field research projects and the instruction of social workers to-be. However, they are usually reduced to the role of informants and not actively taking part as co-partners. For the first time, this anthology gives an overview of courses in which service users and students share their experiences and work together on the same level using gapmending methods. The applications and evaluations of these courses in different European countries are discussed in this volume.